Analisis Hasil Pendukung Keputusan Mendapatkan Rumah Dinas Perusahaan Menggunakan Metode Analytical Hierarchy Process (AHP) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Andi Zulherry; T S Gunawan; Wanayumini Wanayumini (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The Bridgestone company is a company engaged in the plantation sector, currently it has employees of 230 staff/employees, every employee is entitled to an official residence, This requires the company to conduct a decision analysis to determine the official residence for each employee who will apply for the official housing facility. to reduce the level of lack of transparency and accuracy of data that can cause turmoil and gaps for each employee. Then an analysis of the results of decision support for obtaining a company official residence was carried out using the Analytical Hierarchy Process (Ahp) and Technique For Order Preference By Similarity To Ideal Solution (Topsis). The final results of the AHP method trial evaluation result in accurate data where there are 5 employees who are truly in the very feasible category to get an official residence. Whereas in the AHP method there are differences in the results found, where it is found that the number of employees is 1 person who should be in the feasible category but belongs to the very feasible category, so that the number generated from the TOPSIS method is 6 people. With these 2 methods, it can produce an accuracy value of around 60% by entering all the specified criteria.